Eksistensi Hukum Keuangan Negara dalam Peraturan Perundang-Undangan dan Perannya dalam Hukum Pidana - Siska Dwi Andini; Ermania Widjajanti (Bulletin of Community Engagement, 2024)
State financial law is the main key to managing state finances by state administrators. Therefore, it is important to include provisions that specifically regulate state finances and become part of the legal system in Indonesia. The issues addressed in this study include the evolution of state financial law's application in statutory regulations and the ways in which state financial law and criminal law interact. This research applies a qualitative, normative juridical research methodology, examining relevant literature and statutory regulations. This research aims to understand the development of state financial law and its interaction with criminal law. The research results show that state financial law has been incorporated into Indonesia's legal framework, but it has not been fully defined, causing its meaning to change and grow as it is applied. The criminal law for corruption imposes penalties for embezzlement of public funds. It is expected that in the future, the Government and the DPR will be able to promptly enhance the definition and extent of state finances, particularly in Article 23 C of the 1945 Constitution, which serves as the theoretical foundation for state finance provisions. In this way, the spirit of legal reform is felt in both state financial law and criminal corruption law. Ultimately, it is hoped that corruption will be prevented and the space for state administrators to embezzle state funds will be reduced.